Interferon Regulatory Factor 4 Correlated With Immune Cells Infiltration Could Predict Prognosis for Patients With Lung Adenocarcinoma - Li, Xuanzong; Zhai, Shujun; Zhang, Jianbo; Zhang, Dai; Wang, Shijiang; Wang, Linlin; Yu, Jinming (Frontiers in Oncology, 2021)
Background: Immune related interferon regulatory factor 4 (IRF4) is a member of the IRF family, whereas the clinical significance and possible role of IRF4 in lung adenocarcinoma (LUAD) remains unclear. We aimed to investigate the role of IRF4 in predicting the prognosis of LUAD patients. Methods: Using The Cancer Genome Atlas (TCGA) database and our immunohistochemical (IHC) cohort, we analyzed the correlation between IRF4 expression and clinical characteristics, and the prognostic value of IRF4 was also evaluated in LUAD. The potential biological functions of IRF4 in LUAD were analyzed by Gene Set Enrichment Analysis (GSEA). The relationship between IRF4 and immune cell infiltration were evaluated by TISIDB database and our own IHC cohort. In addition, an immune checkpoint inhibitor (ICI) treated cohort from Gene Expression Omnibus database was used to determine the role of IRF4 in LUAD patients with immunotherapy. Results: We found that either mRNA or protein expression level of IRF4 was significantly higher in LUAD than in normal tissues (P < 0.001). The elevate in IRF4 expression in LUAD was significantly associated with the earlier clinical stage (P = 0.002). Patients with LUAD and IRF4 high expression correlated with significant longer overall survival in both TCGA database (P < 0.05) and our IHC-cohort (P = 0.001). Our results also demonstrated that IRF4 could serve as an independent favorable prognostic factor in patients with LUAD. GSEA analysis indicated that high IRF4 expression group enriched with several immune-related pathways, such as B cell receptor signaling pathway, T cell receptor signaling pathway and cytokine-cytokine receptor interaction signaling pathway. In LUAD, IRF4 positively correlated with several different immune infiltrations including various B cells, CD8+ T cells and CD4+ T cells both in mRNA and protein levels. Additionally, we found that the expression of IRF4 was positively associated with PD-1 and PD-L1 mRNA expression levels, and IRF4 high expression predicted better survival in LUAD with immunotherapy (P = 0.071). Conclusions: Our results suggested that IRF4 was associated with higher B cells and T cells infiltration levels and might be a potential favorable prognostic biomarker in LUAD patients with and without immunotherapy.